Photosensitive field emission study of SnS2 nanosheets (27th International Vacuum Nanoelectronics Conference ) - Joshi, Padmashree D.; Joag, Dilip S.; Rout, Chandra Shekhar; Late, Dattatray J. (2014 27TH International Vacuum Nanoelectronics Conference (IVNC), 2014)
SnS2 nanosheets (SnS(2)NSs), synthesized by one-step hydrothermal reaction, are subjected to Field Emission (FE) studies. For synthesis, specific concentrations of Na2SnO3 and thioamide solution are used. The FE study is carried out in all metal Ultra High Vacuum (UHV) chamber in planar diode configuration at a base pressure of similar to 10(-8) torr. A maximum current density of 110 mu A/cm(2) was attainable. The turn on field required to draw a current density of 1 mu A/cm(2) is found to be 2.6 V/mu m. A separate study was carried out to investigate the photosensitivity of the emitter by illuminating the specimen under visible light. In dark, the FN plot is non-linear, indicative of semiconductor nature of the emitter. However, on illumination, the FN plot is observed to be linear. This remarkable change can be explained by the photoconductivity imparted on illumination. The field at the tip is high in presence of light, than in dark, due to enhanced conductivity. It is also observed that on switching ON the light, the FE current increases almost instantaneously. Repetitive switching is observed at a fixed applied voltage, generating current pulses. The visible light soaking of the sample is carried out by illuminating the lamp for more than 100 minutes, where the current seems to saturate. On switching off the lamp the emission current decayed almost to its initial value exponentially. The photosensitivity has been studied for different wavelengths in the visible spectra. The maximum photosensitive field emission is observed for green filter. With this photoresponse, it is envisaged that SnS2 nanosheets are a potential candidate for optoelectronic applications of field emitters.
Keywords: field emission; photosensitivity; Photoswitching

Pulsed laser-deposited MoS2 thin films on W and Si: field emission and photoresponse studies - Late, Dattatray J.; Shaikh, Parvez A.; Khare, Ruchita T.; Kashid, Ranjit V.; Chaudhary, Minakshi V.; More, Mahendra A.; Ogale, Satishchandra B. (ACS Applied Materials & Interfaces, 2014)
We report field electron emission investigations on pulsed laser-deposited molybdenum disulfide (MoS2) thin films on W-tip and Si substrates. In both cases, under the chosen growth conditions, the dry process of pulsed laser deposition (PLD) is seen to render a dense nanostructured morphology of MoS2, which is important for local electric field enhancement in field emission application. In the case of the MoS2 film on silicon (Si), the turn-on field required to draw an emission current density of 10 mu A/cm(2) is found to be 2.8 V/mu m. Interestingly, the MoS2 film on a tungsten (W) tip emitter delivers a large emission current density of similar to 30 mA/cm(2) at a relatively lower applied voltage of similar to 3.8 kV. Thus, the PLD-MoS2 can be utilized for various field emission-based applications. We also report our results of photodiode-like behavior in (n- and p- type) Si/PLDMoS2 heterostructures. Finally we show that MoS2 films deposited on flexible kapton substrate show a good photoresponse and recovery. Our investigations thus hold great promise for the development of PLD MoS2 films in application domains such as field emitters and heterostructures for novel nanoelectronic devices.
Keywords: field emission; MoS2; photodiode heterostructures; pulsed laser deposition; thin film

Perspective on atomically thin 2d inorganic layered materials for biosensor - Late, Dattatray J.; Rout, C. S.; Chakravarty, Disha; Ratha, S. (Journal of Nanomedicine Research, 2015)

Photosensitive field emission study of SnS2 nanosheets - Joshi, Padmashree D.; Joag, Dilip S.; Rout, Chandra Shekhar; Late, Dattatray J. (Journal of Vacuum Science & Technology B, 2015)
SnS2 nanosheets (SnS(2)NSs), synthesized by one-step hydrothermal reaction, are subjected to field emission (FE) studies. For synthesis, specific concentrations of Na2SnO3 and thioamide solutions are used. The FE study is carried out in a planar diode configuration at a base pressure of similar to 10(-8) mbar. The emission photosensitivity is also investigated by illuminating the specimen with a visible light source. In dark, the turn on field, the electric field required to obtain a current density of 1 mu A/cm(2), is found to be 5.9 V/mu m. Upon illumination, the emitter with visible light, it is found to reduce to 5.0 V/mu m. A significant change in the nature of the Fowler-Nordheim plot with light illumination is also observed and has been explained on the basis of photoconductivity. Repetitive switching ON and OFF the light source, at a fixed applied voltage, is found to generate current pulses. The photosensitivity is also studied with various color filters. With the photoswitching and the enhanced field emission properties, it is envisaged that SnS(2)NSs possess a potential for optoelectronic applications of field emitters. (C) 2014 American Vacuum Society.

Pt-nanoparticle functionalized carbon nano-onions for ultra-high energy supercapacitors and enhanced field emission behaviour - Suryawanshi, Sachin R.; Kaware, Vaibhav; Chakravarty, Disha; Walke, Pravin S.; More, Mahendra A.; Joshi, Kavita; Rout, Chandra Sekhar; Late, Dattatray J. (RSC Advances, 2015)
In the present work, we have investigated the charge storage capacitive response and field emission behaviour of platinum (Pt) nanoparticles decorated on carbon nano onions (CNOs) and compared them with those of pristine carbon nano onions. The specific capacitance observed for Pt-CNOs is 342.5 F g(-1), about six times higher than that of pristine CNOs, at a scan rate of 100 mV s(-1). The decoration with Pt nanoparticles, without any binder or polymer separator on the CNO, leading to enhanced supercapacitance is due to easy accessibility of Na2SO4 electrolyte in the active material. The Density Functional Theory (DFT) calculations of these systems reveal enhancement in the Density of States (DOS) near the Fermi energy (E-F) on account of platinum decoration on the CNOs. Furthermore, the field emission current density of similar to 0.63 mA cm(-2) has been achieved from the Pt-CNOs emitter at an applied electric field of similar to 4.5 V mu m(-1) and from the pristine CNOs sample current density of similar to 0.4 mA cm(-2) has been achieved at an applied electric field of similar to 6.6 V mu m(-1). The observed enhanced field emission behavior has been attributed to the improved electrical conductivity and increased emitting sites of the Pt-CNO emitter. The field emission current stability of the Pt-CNO emitter over a longer duration is found to be good. The observed results imply multifunctional potential of Pt-CNOs, as supercapacitor material in various next generation hybrid energy storage devices, and field emitters for next generation vacuum nano/microelectronic devices.

Pulsed laser-deposited nanocrystalline GdB6 thin films on W and Re as field emitters - Suryawanshi, Sachin R.; Singh, Anil K.; Phase, Deodatta M.; Late, Dattatray J.; Sinha, Sucharita; More, Mahendra A. (Applied Physics A-Materials Science & Processing, 2016)
Gadolinium hexaboride (GdB6) nanocrystalline thin films were grown on tungsten (W), rhenium (Re) tips and foil substrates using optimized pulsed laser deposition (PLD) technique. The X-ray diffraction analysis reveals formation of pure, crystalline cubic phase of GdB6 on W and Re substrates, under the prevailing PLD conditions. The field emission (FE) studies of GdB6/W and GdB6/Re emitters were performed in a planar diode configuration at the base pressure similar to 10(-8) mbar. The GdB6/W and GdB6/Re tip emitters deliver high emission current densities of similar to 1.4 and 0.811 mA/cm(2) at an applied field of similar to 6.0 and 7.0 V/mu m, respectively. The Fowler-Nordheim (F-N) plots were found to be nearly linear showing metallic nature of the emitters. The noticeably high values of field enhancement factor (beta) estimated using the slopes of the F-N plots indicate that the PLD GdB6 coating on Wand Re substrates comprises of high-aspect-ratio nanostructures. Interestingly, the GdB6/W and GdB6/Re planar emitters exhibit excellent current stability at the preset values over a long-term operation, as compared to the tip emitters. Furthermore, the values of workfunction of the GdB6/W and GdB6/Re emitters, experimentally measured using ultraviolet photoelectron spectroscopy, are found to be same, similar to 1.6 +/- 0.1 eV. Despite possessing same workfunction value, the FE characteristics of the GdB6/W emitter are markedly different from that of GdB6/Re emitter, which can be attributed to the growth of GdB6 films on W and Re substrates.

PbS nanostar-like structures as field emitters - Pawar, Mahendra S.; Bankar, Prashant K.; More, Mahendra A.; Late, Dattatray J. (Chemistryselect, 2017)
The crystalline PbS nanostars were synthesized by thermal decomposition of thioacetamide (TAA) in aqueous solutions of lead acetate and acetic acid at 80 8 degrees C. The structure and morphology of the PbS nanostars have been characterized using X-Ray Diffraction (XRD), Raman Spectroscopy, Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM). The optical properties of the PbS nanostars have been studied using UV-Visible absorption Spectroscopy (UVVis). The field emission investigations have been carried out on the as synthesized PbS nanostars at the base pressure of similar to 13 10(-8) mbar. The turn on field required to draw an emission current density of 1 mu A/cm(2) is found to be 1.8 V/mm. The emission current-time plots show good emission current stability of the PbS nanostar emitter over a period of 4 hrs. The results in terms of low turn-on field and long term emission current stability of the PbS nanostars emitter reveals that it can be used in field emission based vacuum microelectronics / nanoelectronic devices.

Photo sensor based on 2D materials - Late, Dattatray J.; Bhat, Anha; Rout, Chandra Sekhar (Fundamentals and Sensing Applications of 2D Materials, 2019)
This chapter starts with a general introduction to the interaction of light with matter and use of this principle for sensing. Photo-sensing devices based on two-dimensional (2D) materials are compared to conventional designs and their respective differences discussed in detail. A range of 2D materials are introduced with a generic comparison based on their individual properties and importance to the generation of a photoresponse. Besides transition-metal dichalcogenides, the chapter also deals with black phosphorous photosensor devices. Different heterostructure architectures based on 2D layered structures are investigated and their role in next generation optoelectronics is discussed.

Pressure-induced phase transitions in germanium telluride: raman signatures of anharmonicity and oxidation - Pawbake, Amit; Bellin, Christophe; Paulatto, Lorenzo; Beneut, Keevin; Biscaras, Johan; Narayana, Chandrabhas; Late, Dattatray J.; Shukla, Abhay (Physical Review Letters, 2019)
Pressure-induced phase transitions in GeTe, a prototype phase change material, have been studied to date with diffraction which is not sensitive to anharmonicity-induced dynamical effects. GeTe is also prone to surface oxidation which may compromise surface sensitive measurements. These factors could be responsible for the lack of clarity about the phases and transitions intervening in the phase diagram of GeTe. We have used high-pressure Raman scattering and ab initio pseudopotential density functional calculations to unambiguously establish the high-pressure phase diagram and identify three phases up to 57 GPa, a low-pressure rhombohedral phase, an intermediate pressure cubic phase, and a high-pressure orthorhombic phase. We detect substantial broadening and softening of Raman modes at low pressure and identify the transition regions and possible intermediate phases.